Extrapulmonary sarcoidosis of liver and pancreas: a case report and review of literature - Harder, Hermann; Büchler, Markus W.; Fröhlich, Boris Erwin; Ströbel, Philipp; Bergmann, Frank; Neff, Wolfgang; Singer, Manfred V. (World journal of gastroenterology, 2007)
Sarcoidosis is a chronic multisystemic granulomatous disease of unknown origin, which can involve nearly all organs. In the case of an infrequent gastrointestinal tract involvement in systemic sarcoidosis, granulomas of the liver are most commonly described while isolated pancreatic sarcoid lesions are rarely seen. We report a case of systemic sarcoidosis with exclusive extrapulmonal involvement of the liver and the pancreas in a 71-year-old white man. The diagnosis of liver involvement was confirmed by biopsy. Pancreatic surgery was needed because preoperative evaluation could not exclude pancreatic cancer and for biliary decompression. An extensive literature review of systemic sarcoidosis, focusing on reported cases with unusual presentation of sarcoidosis in the liver and the pancreas, its diagnosis, treatment, and prognosis was made.